(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The article discusses the relevance of increasing the smoothness of the movement of vehicles, and also substantiates the feasibility of using internal suspension of wheels in conjunction with a suspension and as an independent system.